PENGARUH KUALITAS ONLINE TRAVEL AGENT (OTA) TERHADAP LOYALITAS KONSUMEN YANG BERDAMPAK PADA TINGKAT HUNIAN HOTEL (Studi Pada Blitz Hotel Di Tanjung Uncang) - Diana, Nikki Rizka; Arifin, Yoyon (Program Studi Sistem Informasi Institut Indobaru Nasional, 2025)
In expanding marketing, the hotel business cannot only rely on conventional methods but must be assisted by digital applications. Digital marketing applications can be one of the marketing techniques that can reach potential consumers widely. One of these digital-based applications is the Online Travel Agent (OTA).The application used to make reservations at the Blitz Hotel in Tanjung Uncang where the author conducted the research. To determine the effect of the quality of the Online Travel Agent (OTA) on consumer loyalty which has an impact on the hotel occupancy rate, the author conducted research by collecting data through questionnaires. The technique used to carry out the research was by using random sampling. As for data processing using a quantitative approach, descriptive method, validity test, reliability test and multiple linear regression analysis using the Slovin formula. The results of the study indicate that the influence of the quality of the Online Travel Agent (OTA) has a positive effect on consumer loyalty which has an impact on the occupancy rate of the Blitz Hotel in Tanjung Uncang.